Problems with the implementation of Adat Basandi Syarak Syarak Basandi Kitabullah philosophy - Asrinaldi Asrinaldi; Yoserizal Yoserizal (Faculty of Social and Political Science, Universitas Airlangga, 2020)
This study discusses the problems of West Sumatra’s local governments in the practice and implementation of Adat Basandi Syarak Syarak Basandi Kitabullah (ABS-SBK) tradition philosophy in the West Sumatra regional medium-term development plan in 2016-2021. The purpose is to organize the program and activities developed in the regional budget. This study analyzes the ABS-SBK tradition philosophy practice in West Sumatra government administration. This study uses a descriptive qualitative method; moreover, the data collection in this study uses semi-structured interviews related to the practice of ABS-SBK tradition philosophy. This study interviewed 14 informants consisting of customary stakeholders, religious leaders, bureaucrats, academics, women (bundokanduang), and community leaders. In determining the informants, this study uses a purposive sampling method conducted in Agam Regency and Limapuluh Kota Regency in West Sumatra Province. This study found that four factors influence the implementation and practice of the ABS-SBK tradition philosophy in the government level: 1) the absence of apparent ABS-SBK tradition philosophy substance values, 2) the traditional transcendental and profane values of the traditional and sharia institution did not work very well in maintaining and preserving Minangkabau traditional values, 3) the absence of individual consensus and commitment toward ABS-SBK philosophy, and 4) the poor and minimum ABS-SBK tradition philosophy implementation at the government level. People interpret and translate this philosophy according to their understanding since no specific guidelines govern their interaction. This fact is understandable and reasonable since it is part of their life. The same goes for the government level, the absence of the guidelines causes a poor and minimum effort in their development program using ABS-SBK tradition philosophy as the basic. It also leads to a consensus between customary and religious institutions. The government finds it challenging to translate this philosophy into their programs and activities development so that they cannot directly refer their programs to this original philosophy from Minangkabau.